Mapping the plasmon response of Ag nanoislands on graphite at 100 nm resolution with scanning probe energy loss spectroscopy. (13th November 2015) - Murphy, Shane; Bauer, Karl; Sloan, Peter A.; Lawton, James J.; Tang, Lin; Palmer, Richard E.
Abstract: We demonstrate plasmon mapping of Ag nanostructures on graphite using scanning probe energy loss spectroscopy (SPELS) with a spatial resolution of 100 nm. In SPELS, an STM tip is used as a localized source of field-emitted electrons to probe the sample surface. The energy loss spectrum of the backscattered electrons is measured to provide a chemical signature of the surface under the tip. We acquire three images simultaneously with SPELS: i) constant-current field-emission images, which provide topographical information; ii) backscattered electron images, which display material contrast; and iii) SPELS images, where material-dependent features such as plasmons are mapped.